63.0k views
1 vote
MY LAST QUESTION REALLY NEED HELP

Use the table below to answer this question:

X Y
---------------
-1 -3
0 -1
2 3

Find the average rate of change for the given function from x = −1 to x = 2.

A. -2
B. -1
C. 1
D. 2

User Lianna
by
5.8k points

1 Answer

4 votes
average rate of change is just the slope between the points

the average rate of change from x=-1 to x=2 is
(f(2)-f(-1))/(2-(-1))

given
f(2)=3
f(-1)=-3


slope=(3-(-3))/(2-(-1))=(3+3)/(2+1)=6/3=2
average rate of change is 2

D is answer
User Jamesfdearborn
by
5.7k points